ANALYSIS OF CHECK-IN COUNTER SERVICE PERFORMANCE USING THE QUEUE METHOD AT HUSEIN SASTRANEGARA AIRPORT - Rahmana, Arief; Rahmanto, Eko Arif; Purbaya, Dian Galih (CENTRAL ASIA AND THE CAUCASUS, 2022)
The airport is a very vital facility that exists in every country that functions as a gateway to be able to connect between islands and countries. With this very vital function, it is necessary to have several checks to be able to enter the airport. One of the services at the airport is the Check-in Counter, which is a place where passengers get their boarding passes and weigh their baggage to be labeled and put on the plane. At check-in, the passenger must submit his ticket and identity to the check-in counter for inspection. After checking in and obtaining a boarding pass, the passenger is allowed to enter the waiting room (boarding gate). Optimizing check-in counter services is a very important part of the airport service stage. To find out this can use analysis using the queuing method to be able to optimize the service process at the Check-in Counter. The initial data used in processing is the average number of consumer arrivals and service time at the check-in counter. The results of this study indicate that the service conditions are still good because the level of utilization is still <1. The average consumer who queues is 3 people per hour and the time needed to queue is 27.86 minutes. Meanwhile, the time needed to complete the Check-in Counter facility service is 42.86 minutes